Isupo: Assessing the relevance of Deuteronomy 25:5–10 in the Nigerian Christian context, with particular reference to the Yoruba - Ademiluka, Solomon O. (HTS teologiese studies, 2023)
The description of levirate marriage in Deuteronomy 25:5–10 has reminiscences with the same practice in Africa, especially isupo (levirate marriage) among the Yoruba of south-west Nigeria. The article seeks the relevance of this text in Nigeria in the possibility of levirate marriage still being of some socio-economic value to Christian widows and the society at large. It employs the historical-critical and descriptive methods. The work finds that in both the Hebrew and African cultures, levirate marriage served the purpose of raising children for the deceased, who would perpetuate his lineage and inherit his property. But in Africa the institution was most significant in providing economic and social protection for widows and their children. Unfortunately, levirate marriage is fast disappearing in Nigeria because of Western influence, particularly Christianity. The effect of this for many widows is abject poverty, by virtue of which some of them resort to illegitimate and dishonouring means to make ends meet. The work, therefore, concludes that resuscitating levirate marriage would be of immense socio-economic value to Nigerian widows and the society.Contribution: The article is a contribution to Old Testament theology and Christian ethics. It proposes that levirate marriage can still be employed as a means of socio-economic protection for Nigerian Christian widows.